2012
DOI: 10.1088/1748-9326/7/4/045803
|View full text |Cite
|
Sign up to set email alerts
|

The water implications of generating electricity: water use across the United States based on different electricity pathways through 2050

Abstract: The power sector withdraws more freshwater annually than any other sector in the US. The current portfolio of electricity generating technologies in the US has highly regionalized and technology-specific requirements for water. Water availability differs widely throughout the nation. As a result, assessments of water impacts from the power sector must have a high geographic resolution and consider regional, basin-level differences. The US electricity portfolio is expected to evolve in coming years, shaped by v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
160
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(161 citation statements)
references
References 13 publications
1
160
0
Order By: Relevance
“…The combination of the calibrated baseyear data on electricity final energy demand with the water withdrawal and consumption coefficients from Macknick et al (2012Macknick et al ( , 2011 and the cooling shares from , result in a good fit of our water demand baseyear values (496 km 3 /year for withdrawal, 26 km 3 /year for consumption excluding hydropower, and 50 for hydropower consumption, Figure 2) …”
Section: The Remind Modelmentioning
confidence: 82%
See 3 more Smart Citations
“…The combination of the calibrated baseyear data on electricity final energy demand with the water withdrawal and consumption coefficients from Macknick et al (2012Macknick et al ( , 2011 and the cooling shares from , result in a good fit of our water demand baseyear values (496 km 3 /year for withdrawal, 26 km 3 /year for consumption excluding hydropower, and 50 for hydropower consumption, Figure 2) …”
Section: The Remind Modelmentioning
confidence: 82%
“…Water withdrawal and consumption coefficients per electricity output are based on Macknick et al (2012Macknick et al ( , 2011 and shown for the REMIND technologies in SM Table 1. These coefficients have been utilized by numerous studies in the literature analyzing water demand for electricity generation (e.g.…”
Section: The Remind Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that the water-use constraint could also impact the generation mix and the choice of cooling technology. & Different levels of reductions in energy-system-wide CO 2 emissions Cameron et al evaluated the effects of reducing the energy-system-wide CO 2 emissions by 10 %, 25 %, and 50 % on water use for the US electric power sector [24•]. For the 10 % and 25 % reduction scenarios, the electric power sector account for nearly all of the systemwide reductions.…”
Section: Water Impacts Of Low-carbon Electricity Generationmentioning
confidence: 99%